5+44x=53+8x

Simple and best practice solution for 5+44x=53+8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+44x=53+8x equation:


Simplifying
5 + 44x = 53 + 8x

Solving
5 + 44x = 53 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
5 + 44x + -8x = 53 + 8x + -8x

Combine like terms: 44x + -8x = 36x
5 + 36x = 53 + 8x + -8x

Combine like terms: 8x + -8x = 0
5 + 36x = 53 + 0
5 + 36x = 53

Add '-5' to each side of the equation.
5 + -5 + 36x = 53 + -5

Combine like terms: 5 + -5 = 0
0 + 36x = 53 + -5
36x = 53 + -5

Combine like terms: 53 + -5 = 48
36x = 48

Divide each side by '36'.
x = 1.333333333

Simplifying
x = 1.333333333

See similar equations:

| 7=9x-7 | | 7z-7=5+32 | | b=4b | | 34.95(5)+x(.49)=200 | | 6+7x=-8 | | 3(x-6)=2 | | -11-5(t-3)= | | y=(x^2+1)(12x)-(6x^2+7)(2x) | | 44-5x=53-8x | | 7(x-2)+2=-12 | | .10x+.35(50)=23.5 | | 4y+6=8y+2 | | 13x-203=6x-7 | | 5+2t-2=6t+9-2t | | 10.4+3.2f=5f+4 | | 4x-6=4(x+1) | | 3(-9)+2= | | -6x-17=-125 | | -23+22=m-4 | | v-7.92=1.9 | | 31-(3x+5)=3(x+4)+x | | 10x-17=12x+21 | | -0.6x-0.3x+8=-1 | | 12x-5=7x+50 | | x-8.2=4.5 | | 9r-6r+6=6r+6-r | | -2w-4w-24=48 | | 736=4(x+18) | | 2y-15=85-3y | | 6r+4=26r+9 | | 9x+42+15x=4y-13 | | 5(-x)-5= |

Equations solver categories